2009
DOI: 10.1177/1753193408103498
|View full text |Cite
|
Sign up to set email alerts
|

Use of Wolfe Graft for the Treatment of Mucous Cysts

Abstract: Many surgical procedures have been described for the treatment of mucous cysts. We report a case series of a surgical technique that excises the cyst along with overlying skin and reconstructs the defect using a Wolfe graft harvested from the wrist crease. This technique can be applied to cysts in all locations, even those adjacent to the nail. The procedure has been performed on 51 mucous cysts with satisfactory results, a very low recurrence rate (4%) and negligible complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Recurrence of the digital mucous cyst is common; procedures with identification and ligature of one or more pedicles (intraarticular methylene blue injection allows a good visualization), partial capsulectomy, and removal of osteophytes increase the The surgical excision technique followed by self-grafting is a therapeutic option, as it allows reconstructing lesions in different topographies and sizes, with recurrence rates varying from 3.3 to 4%. 4,5 Other surgical treatments that have been described…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of the digital mucous cyst is common; procedures with identification and ligature of one or more pedicles (intraarticular methylene blue injection allows a good visualization), partial capsulectomy, and removal of osteophytes increase the The surgical excision technique followed by self-grafting is a therapeutic option, as it allows reconstructing lesions in different topographies and sizes, with recurrence rates varying from 3.3 to 4%. 4,5 Other surgical treatments that have been described…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment strategies for digital mucous cyst remain controversial (1,2,4,5), excision of such cysts is performed commonly, and new methods that can simplify the procedure and reduce complications and recurrence are desired. In applying our proximal nail fold flap technique, we found that excision of the stalk, joint capsule and any osteophyte was easily achieved under the wide operative field obtained after elevation of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…Such cysts are sometimes painful and interfere with a person's daily activities. When the skin covering the cyst at the proximal nail fold is very thin and easily torn, the skin is often excised along with the cyst, and a skin flap or skin graft is transferred to the skin defect (1,2). Patients must rest the finger for several days after this surgery.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cyst excision with osteophyte excision may substantially reduce the risk of recurrence (Brown et al, 1991;Eaton et al, 1973;Fritz et al, 1997;Kasdan et al, 1994;Kleinert et al, 1972;Rizzo and Beckenbaugh, 2003), but at the risk of subsequent infection or wound problems. Thorough debridement and en block cyst excision raises concerns about thin, eroded skin or skin defects and injury to the germinal matrix, and although many authors have reported good results of skin grafts (Constant et al, 1969;Jamnadas-Khoda et al, 2009), flaps or flap advancement (Shin and Jupiter, 2007;Young and Campbell, 1999) for the treatment of skin erosion or defects, these require additional procedures and cause donor site morbidity. Gingrass et al (1995) reported complete resolution of mucous cysts with associated nail deformities after osteophyte excision conducted as described by Lowrey and Shepler, and Budoff (2010) recommended not dissecting out cysts or removing cyst walls unless the amount of non-viable skin is large.…”
Section: Discussionmentioning
confidence: 99%